The Impact of Cyberattacks on Jakarta's Electric Energy Sector: An Evaluation of Risk, Security, and Economic Implications - Ismail Zaky Al Fatih; Arthur Josias Simon Runturambi; Stepi Anriani (Journal Of Social Science (JoSS), 2024)
This research explores the impact of cyberattacks on the electric energy sector in Jakarta. Cyberattacks are increasingly becoming a serious threat to critical infrastructure, including energy systems, affecting the stability and security of electricity supply. The purpose of this study is to evaluate the risk and vulnerability of Jakarta's electrical energy infrastructure to cyberattacks, and to analyze the economic implications of potential disruptions. Using secondary data from scientific journals and agency reports, this study identified Jakarta's high vulnerability to cyber-attacks, particularly in Industrial Control Infrastructure (ICS) and SCADA. The analysis shows that cyber-attacks can cause significant disruptions to electricity supply, having far-reaching impacts on various sectors including transportation, health, and the economy. Key findings highlight the need for stronger security strategies, effective risk mitigation, and increased public awareness. The research provides recommendations for strengthening public policy and investment in the security of electrical energy infrastructure, and underscores the importance of effective communication in managing public expectations and preparation for potential disruptions. This research paves the way for further research in several areas, including the development of innovative cybersecurity technologies and the analysis of the long-term impact of cyberattacks on Jakarta's economic and social stability. Collaborative efforts between the government, private sector and the community are needed to improve resilience to cyberattacks in the electric energy sector.